Intern doctors’ views on the current and future antibiotic resistance situation of Chattagram Maa O Shishu Hospital Medical College, Bangladesh - Hoque R; Mostafa A; Haque M (Dove Medical Press, 2015)
Rozina Hoque,1 Asma Mostafa,2 Mainul Haque3 1Department of Pharmacology, 2Department of Anatomy, Chattagram Maa O Shishu Hospital Medical College, Agrabad, Chittagong, Bangladesh; 3Unit of Pharmacology, Faculty of Medicine, Universiti Sultan Zainal Abidin, Terengganu, Malaysia Background: Bacterial resistance due to antibiotic misuse is reported every day. Such threat calls for a consensus to develop new strategies to prevent the development of antibiotic resistance of bacteria. Medical doctors must play a pivotal role to control and prevent the misuse of antibiotics. There were complaints that prescribers are lacking behind in updates and advancement in the field. To address such knowledge gap, a study was conducted to know the views of interns on the current antibiotic resistance situation in a teaching hospital in Bangladesh. Methods: This study was a cross-sectional, randomized, and questionnaire-based survey. Interns of the medicine, gynecology, and surgery departments of Chattagram Maa O Shishu Hospital Medical College were the study population. Results: Out of 50 respondents, 98% would like more education on antibiotic selection. All respondents believed that prescribing inappropriate or unnecessary antibiotics was professionally unethical. Ninety percent of the participants were confident in making an accurate diagnosis of infection. Eighty-four percent of them were confident about dosage schedule. In all, 98% participants thought that antibiotic resistance is a national problem and 64% of the respondents thought that same problem also existed in their hospital. Study participants were of the view that 41%–60% of antibiotic usages are irrational in Bangladesh. Fifty-eight percent of the study population thought that antimicrobial resistance (AR) would be a greater problem in the future. Conclusion: The interns believe that there is a knowledge gap on AR. More emphasis should be given to AR and its implications in the undergraduate curriculum. Latest national and international guidelines for antimicrobial therapy and resistance should be made available to the interns. Keywords: interns, antibiotic, prescribing, resistance, Bangladesh, knowledge, perception